Processo contraditório de uso e ocupação em Áreas de Preservação Permante, às margens do rio Poti - Teresina, PI - Costa, Renato Sérgio Soares [UNESP] (2015)
Society's characteristics are reflected directly in the spatial arrangement of the city, in the way people live, work and travel in their daily lives. In the modern city, a product of the market economy, it is common to attempt to agglutination of the population according to economic strata, with people seeking proximity to their counterparts. Where different actors, each centered mainly on spatial strategies and practices of spatial enhancement, however, expanding throughout the country, including in Permanent Preservation Areas - APP. In line with the goals we sought initially in the literature, the theoretical basis for the theme to be developed, and the procedures to be adopted in the treatment of quantitative statistical data presented in the form of thematic maps. We conceptualize terms which we believe are necessary, their respective, understandings in the analysis of this research. In the final considerations, we point out a methodological theoretical analysis relevant to a new urban redirection based on a Critical Geography spatial construction for a quality of life in Teresina. Where prevails the construction and reconstruction of space and continues its analysis